A Study of the Factors Contributing to EFL Speaking Anxiety at Zawiya University (Comprehensive Journal of Science, 2026)
The major aim of this study is to investigate the main causes of speaking anxiety among first semester students at Zawiya University. A Sample of 55 students who were  chosen randomly from the whole number of the first semester students at the English department were the participants. Data was collected by using a questionnaire. This questionnaire aims to answer the main research question: what are the main causes of speaking anxiety among first semester students at Zawiya University. The collected data was analyzed by using SPSS program and discussed in relation to the research question of this study. The findings of this study show that the main causes of speaking anxiety are communication apprehension (CA), the fear of negative evaluation (FNE) and low self-confidence (LSC). The results also show that anxiety is one of the factors which are responsible of students under achievement and low performance.